2016
DOI: 10.1186/s40064-016-3513-6
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic diversity and population differentiation of small giant clam Tridacna maxima in Comoros islands assessed by microsatellite markers

Abstract: Small giant clam, Tridacna maxima, widely distributed from French Polynesia to East Africa, has faced population declines due to over-exploitation. Comoros islands are an important biogeographic region due to potential richness of marine species, but no relevant information is available. In order to facilitate devising effective conservation management plan for T. maxima, nine microsatellite markers were used to survey genetic diversity and population differentiation of 72 specimens collected from three Comoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
6
0
4
Order By: Relevance
“…The high genetic distinctiveness of the Red Sea lineages, especially in T. squamosa , suggest possible cryptic species (Hui et al, ). In the southern part of the WIO, apart from a single genetic study on the connectivity of T. maxima populations from the Comoros Islands (Mohamed et al, ), and two ecological studies on T. maxima and T. squamosa around Mauritius (Ramah, Taleb‐Hossenkhan, & Bhagooli, ; Ramah, Taleb‐Hossenkhan, Todd, Neo & Bhagooli, ), little attention has been paid to giant clams of this least known biogeographical province (Wafar, Venkataraman, Ingole, Ajmal Khan, & LokaBharathi, ) despite its high species richness (Costello et al, ; Hoareau, Boissin, Paulay, & Bruggemann, ). Cryptic species and/or highly genetically divergent peripheral populations have been revealed in the Red Sea and the WIO provinces in many groups (Berumen et al, and references therein), which contributed to the view that these provinces are marine biodiversity and evolutionary hotspots (Borsa et al, ; Hoareau et al, ; Obura, ; Ramírez, Afán, Davis, & Chiaradia, ; Roberts et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The high genetic distinctiveness of the Red Sea lineages, especially in T. squamosa , suggest possible cryptic species (Hui et al, ). In the southern part of the WIO, apart from a single genetic study on the connectivity of T. maxima populations from the Comoros Islands (Mohamed et al, ), and two ecological studies on T. maxima and T. squamosa around Mauritius (Ramah, Taleb‐Hossenkhan, & Bhagooli, ; Ramah, Taleb‐Hossenkhan, Todd, Neo & Bhagooli, ), little attention has been paid to giant clams of this least known biogeographical province (Wafar, Venkataraman, Ingole, Ajmal Khan, & LokaBharathi, ) despite its high species richness (Costello et al, ; Hoareau, Boissin, Paulay, & Bruggemann, ). Cryptic species and/or highly genetically divergent peripheral populations have been revealed in the Red Sea and the WIO provinces in many groups (Berumen et al, and references therein), which contributed to the view that these provinces are marine biodiversity and evolutionary hotspots (Borsa et al, ; Hoareau et al, ; Obura, ; Ramírez, Afán, Davis, & Chiaradia, ; Roberts et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of giant clam species have measured the genetic diversity at large spatial scales across the Indo‐Pacific region (Nuryanto & Kochzius, 2009; Neo & Todd, 2012; DeBoer et al, 2014; Hui et al, 2016; Hui, Nuryanto & Kochzius, 2017; Keyse et al, 2018); however, genetic differentiation can be detected at local scales; for example, Comoros Islands (Mohamed et al, 2016), oceanic New Caledonia islands and Vanuatu archipelago (Van Wynsberge et al, 2017b). Interestingly, this study demonstrated that both giant clam species exhibited low but significant genetic differentiation, with different patterns of genetic structure at the local‐scale scenario of PMP and Rhu Island.…”
Section: Discussionmentioning
confidence: 99%
“…Semua spesies Tridacna mengalam i tahap larva planktotrophic pada siklus hidupnya sebelum menjadi spesies bentik (Lucas, 1988). Larva dispersal Tridacna dapat menghabiskan waktu hingga 9-19 hari (Jameson, 1976;Mies & Sumida, 2012;Triandiza & Kusnadi, 2013;Mohamed et al, 2016) melayang mengikuti arus sebelum menetap di substrat yang keras. Aliran genetik yang dibawa pada tahap kehidupan planktonik ini berpotensi untuk terdistribusi ke populasi yang jauh dan melakukan percampuran genetik antar populasi melalui perkawinan acak.…”
Section: Implikasi Konservasiunclassified